PH/Thermosensitive dual-responsive hydrogel based sequential delivery for site-specific acute limb ischemia treatment. Issue 38 (7th September 2022) - Zhang, Teng; Ouyang, Huan; Liu, Shichen; Xiong, Lei; Zhong, Zhiwei; Wang, Qingqing; Qiu, Zhuang; Ding, Yajia; Zhou, Weimin; Wang, Xiaolei
Abstract : A nanoplatform was developed to respond the changes of two different phases of acute limb ischemia, sequential releasing of drugs thus could be realized automatically to achieve in time cytoprotective and angiogenesis effects. Abstract : Acute limb ischemia (ALI) is the most severe manifestation of peripheral artery disease, accompanied by pH/temperature-microenvironment changes in two different phases. In the acute phase, temperature and pH are significantly decreased, and reactive oxygen species (ROS) are excessively generated owing to the sharp reduction of blood perfusion. Afterwards, in the chronic phase, although the temperature gradually recovers, angiogenesis is delayed due to chronic vascular injury, skeletal muscle cell apoptosis and endothelial cell dysfunction. Current therapeutic strategies mainly focus on recanalization; however, their effects on scavenging ROS in the acute phase and promoting angiogenesis in the chronic phase are quite limited. Herein, an injectable pH and temperature dual-responsive poloxamer 407 (PF127)/hydroxymethyl cellulose (HPMC)/sodium alginate (SA)-derived hydrogel (FHSgel), encapsulating melatonin and diallyl trisulfide-loaded biodegradable hollow mesoporous silica nanoparticles (DATS@dHMSNs), is developed, which can intelligently respond to the different phases of ALI. In the acute phase of ischemia, the decreased pH results in the rapid release of melatonin to scavenge excessive ischemia-induced ROS. On the other hand, in the chronic repair phase, the recovered temperature triggers the sustained release of DATS@dHMSNs from the FHSgel, thus generating hydrogen sulfide (H2 S) to enhance the angiogenesis and microcirculation reconstruction of ischemic limbs.